A rare cause of diarrhoea: uncommon effect of an ordinary medication - Costa, Rafaela (2022)
Introduction: Arterial hypertension is a chronic condition and one of the main risk factors for cardiovascular disease. Therefore, patients presenting with this disorder benefit from regular follow-ups with their general practitioner/family doctor (FD). Blood pressure control can be achieved with lifestyle measures alone or by resorting simultaneously to pharmacological treatment. Among pharmacological options, angiotensin II receptor blockers (ARB) stand out for being commonly used due to their anti-hypertensive effect and safety profile, albeit they can rarely cause severe chronic diarrhoea. This case report intends to present a rare diagnosis and sharpen FD to a new diagnostic hypothesis in the face of chronic diarrhoea. Case report: A 65-year-old woman, with a personal history of arterial hypertension treated with olmesartan 20mg since 2012 and no other relevant personal history. The patient presented with a one-month history of diarrhoea entailing several medical evaluations. Along with abdominal pain, nausea, vomiting, asthenia, and weight loss. Due to an inconclusive outpatient investigation and lack of clinical response to the multiple empirical treatments, the patient was proposed for hospital admission for further etiological study. While hospitalized, olmesartan was discontinued resulting in symptom resolution, which lead to patient discharge with the diagnosis of sprue-like enteropathy. Conclusion: This case intends to emphasize the importance of a complete and detailed medical history, recall the main steps in the investigation of chronic diarrhoea and disclose a rare diagnosis of sprue-like enteropathy olmesartan-induced. According to the European definition of general practice/family medicine, the FD is responsible for the longitudinal continuity of care which will involve the reassessment and monitoring of the clinical condition. Furthermore, once faced with this diagnosis, FD is encouraged to overcome the challenge of ulterior blood pressure control.